Formation et soutien à l’apprentissage : des conditions indispensables à la polyvalence et à la santé et sécurité au travail - Céline Chatigny; Nicole Vézina; Johanne Prévost (Perspectives Interdisciplinaires sur le Travail et la Santé)
The objective of this study conducted in an automobile assembly plant was to identify the types of job training situations and to understand how they are experienced. Observations accompanied the interviews with male and female workers as well as with representatives of the company and union. The results show that training improved in duration and content, but that the increased production requirements constantly recreate a gap between the training offered and that required by the workers that were met. These gaps are particularly problematic for the most versatile workers with precarious employment, particularly women. Learning is often done at a cost that eats away at health, confidence and the motivation to learn, particularly in job rotation implementation situations.